Assessing the relationship between a web application-based load and recovery score and training load, considering the menstrual cycle: A longitudinal observational study in elite women's soccer - Stefanie L. Brefin; Jan Anderegg; Claudio R. Nigg; David Koschnick; Claudia Paul; Sascha Ketelhut (Bern Open Publishing, 2024)
Introduction Recovery monitoring is a fundamental component for continuous performance enhancement in sports and exercise (Bourdon et al., 2017). Given that recovery is considered a multifaceted restorative process, various physiological and psychological measures should be tracked daily (Heidari et al., 2018). Digital applications can aid in effortlessly collecting, integrating, and summarizing this data. In a collaborative research project, a web application was developed to monitor the load and recovery of athletes engaged in team sports. This study assesses the relationship between the web-application-based Load and Recovery Score (LRS) and training load among elite female soccer players in Switzerland. Furthermore, it explores the potential influence of the menstrual cycle on the individual training responses of these players. Methods A total of 49 female soccer players (age: 19 ± 2 years, height: 166 ± 5 cm, body mass: 59 ± 5 kg) were recruited for this 6-week longitudinal observational study. The LRS was recorded daily using a web application, and players recorded their basal temperature each morning. Training load was assessed based on trainer-intended ratings of perceived exertion. Linear mixed models were employed, accounting for individual responses as random effects in the analysis. Results A significant negative relationship was found between training load and players' LRS (Est. = -0.009, 95% CI -0.011, -0.007, p < .001). When controlling for training load, no significant effect of the menstrual cycle on players' LRS was found (F = 1.274, p = .283). Variance explained by the residual factor of both models was 46.59% and 50.07%, respectively, with a high proportion of variance attributed to random effects (43.67%, and 47.43% respectively). Discussion/Conclusion The LRS appears to be a practical tool for monitoring load and recovery status in women's soccer. Its ability to depict training load at an individual and multifactorial level can assist coaches in recognizing players' responses to training. However, further studies that determine the relationship between the LRS and other load and recovery parameters are highly warranted. The menstrual cycle did not show a significant effect on the LRS. Hence, the sensitivity of the LRS to menstrual cycle phases and its overall influence on recovery processes remains questionable. Nonetheless, we recommend systematic monitoring of the menstrualcycle as an extension of the LRS, as irregularities or the absence of menstrual bleeding may indicate serious health issues. References Bourdon, P. C., Cardinale, M., Murray, A., Gastin, P., Kellmann, M., Varley, M. C., Gabbett, T. J., Coutts, A. J., Burgess, D. J., Gregson, W., & Cable, N. T. (2017). Monitoring athlete training loads: Consensus statement. International Journal of Sports Physiology and Performance, 12(Suppl 2), S2161-S2170. https://doi.org/10.1123/IJSPP.2017-0208 Heidari, J., Beckmann, J., Bertollo, M., Brink, M., Kallus, W., Robazza, C., & Kellmann, M. (2019). Multidimensional monitoring of recovery status and implications for performance. International Journal of Sports Physiology and Performance, 14(1), 2-8. https://doi.org/10.1123/ijspp.2017-0669